Peningkatan Keterampilan Passing Bawah Bola Voli Siswa Kelas X Melalui Model Pembelajaran Project Based Learning - Mariani Agustini Raaiyatini; Sunarno Basuki; Mashud Mashud; Pebriyandi Pebriyandi; Sahbana Ridha (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. The purpose of this study was to improve lower passing skills by using the Project Based Learning (PjBL) learning model. Materials and Methods. The Kurt Lewin model research design is a research design consisting of four stages, namely, planning, implementation, observation, and reflection. The research subjects were class X students of SMKN 1 Pandih Batu, totaling 15 people. The object of research was the improvement of volleyball lower passing skills by using the Project Based Learning (PjBL) learning model. The instrument used in this research was the lower passing skill performance test instrument. The data analysis used was quantitative and qualitative descriptive analysis. Results. Based on data analysis, the results of learning volleyball lower passing showed an increase in volleyball lower passing skills. This is indicated that in cycle I only 9 people or 60% of students who were complete and 6 people or 40% of students who were not complete, then in cycle II there was an increase, namely from 15 students who completed 11 people or 73% of students who were complete and 4 people or 27% of students who were not complete. Conclusion. The learning outcomes of volleyball lower passing skills have seen an increase from cycle I and cycle II using the volleyball lower passing learning model has increased overall.